UJI RETENSI DAN EFEKTIVITAS TANAMAN KUMIS KUCING (Orthosiphon aristatus) TERHADAP SERANGAN RAYAP TANAH (Coptotermes sp) PADA KAYU DURIAN (Durio zibethinus) - Mariana, Eka; Ariyanti, Ariyanti; Erniwati, Erniwati (Universitas Tadulako, 2013)
Nowadays, utilization ofnon-durable wood species in Indonesia is one alternative to meet the needs ofthe wood. Use natural preservatives such as Orthosiphon aristatus in natural wood preservation processis highly recommended as environmentally friendly.This study was aimed to determine retention and the effects of Orthosiphon aristatus leaves extracts as preservation material of Durio zibethinus wood on the Coptotermes sp. Attacks. Regency and the laboratory of Forestry Science, Tadulako University, from May to June 2013. The study was using completely randomized design with factorial pattern. The treatment of study was applying two factors. First, concentration of Orthosiphon aristatus extracts with three levels, namely; 9.09% (A1), 16,67% (A2), and 23,07% (A3). Second, Dipping time with three levels,namely: 1 day (B1), 3 days (B2), and 5 days (B3). The results showed that the highest retention value (3,538g/cm3) was achieved by the combination treatment between concentration 23,07% and dipping time 5 days (A3B3) while the lowest retention value (0,562g/cm3) was achieved by the combination treatment between concentration 9,09% and dipping time 1 day (A1B1). Hence, the lowest effectivity of preservation materials indicated by the highest weight loss,was achieved by A1B1 combination treatment (3,37%) while the lowest (highest effectivity) was achieved by (A3B3) combination treatment (1,88%). Keywords: Concentration, Dipping time, Orthosiphon aristatus, Durio zibethinus, Coptotermes sp.